2022
DOI: 10.1088/2057-1976/ac4f97
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric comparative analysis of Brainlab elements and Eclipse RapidArc for spine SBRT treatment planning

Abstract: Purpose: This is a dosimetric study comparing stereotactic body radiotherapy (SBRT) plans of spine tumors using Brainlab Elements Spine planning module against Eclipse RapidArc plans. Dose conformity, dose gradient, dose fall-off, and patient-specific quality assurance (QA) metrics were evaluated. Methods: Twenty patients were immobilized in supine position using half Vac‐Lok. A prescription dose of 16 Gy in a single fraction was planned for Varian TrueBeam. Conformal arc plans were generated with Pencil beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The authors also noted an improvement of PCI and GI when using Elements Spine SRS, with the same beam geometry in both TPS but with duplication option in Spine SRS. In another study, the same TPS were compared, but using different algorithms for final dose calculation (AcurosXB for Eclipse TPS; Pencil Beam and MC algorithms for Spine SRS) [7]. Similar to us, they found a significant difference on spinal cord sparing, and on the maximum dose to the CTV with on average a maximum dose 1.6 Gy higher in Spine SRS using MC algorithm.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The authors also noted an improvement of PCI and GI when using Elements Spine SRS, with the same beam geometry in both TPS but with duplication option in Spine SRS. In another study, the same TPS were compared, but using different algorithms for final dose calculation (AcurosXB for Eclipse TPS; Pencil Beam and MC algorithms for Spine SRS) [7]. Similar to us, they found a significant difference on spinal cord sparing, and on the maximum dose to the CTV with on average a maximum dose 1.6 Gy higher in Spine SRS using MC algorithm.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have compared E-SRS with other VMAT solutions [6], [7], [8], [9]. In a first study, similar dosimetric results were found on the dose to the spinal cord and to the PTV, when comparing the E-SRS with Eclipse TPS (AAA algorithm) [6].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…To circumvent the planning optimization difficulty for SBRT spine treatment, Brainlab (Munich, Germany) created a dedicated spine optimization algorithm, that is, built into their Elements Spine SRS v3.0 treatment planning system. The algorithm is tailored for the concave geometry of SBRT spine and has been shown to produce plans with improved conformity and gradient indices while reducing spinal cord dose 12–17 …”
Section: Introductionmentioning
confidence: 99%